Teaching and learning in the digital age - Starkey, Louise (New York, N.Y. : Routledge, 2012)
Teaching and Learning in the Digital Age is for all those interested in considering the impact of emerging digital technologies on teaching and learning. It explores the concept of a digital age and perspectives of knowledge, pedagogy and practice within a digital context